British nuclear test veteran family trios for the study of genetic risk. (1st June 2022) - Rake, Christine; Gilham, Clare; Scholze, Martin; Bukasa, Laurette; Stephens, Jade; Simpson, Jayne; Peto, Julian; Anderson, Rhona
Abstract: The risk of radiation effects in children of individuals exposed to ionising radiation remains an ongoing concern for aged veterans of the British nuclear testing programme. The genetic and cytogenetic family trio (GCFT) study is the first study to obtain blood samples from a group of British nuclear test veterans and their families for the purposes of identifying genetic alterations in offspring as a consequence of historical paternal exposure to ionising radiation. In this report, we describe the processes for recruitment and sampling, and provide a general description of the study population recruited. In total, blood samples were received from 91 (49 test and 42 control) families representing veteran servicemen from the army, Royal Air Force and Royal Navy. This translated to an overall response rate of 14% (49/353) for test veterans and 4% (42/992) for control veterans (excluding responders known to be ineligible). Due to the lack of dose information available, test veterans were allocated to a three-point exposure rank. Thirty (61%) test veterans were ranked in the lower group. Nineteen (39%) of the 49 test veterans were classified in the mid (5 veterans; 10%)/high (14 veterans; 29%) exposure ranks and included 12 veterans previously identified as belonging to the special groups or listed in health physics documents. An increased number of test veteran families (20%), compared with control families (5%), self-reported offspring with congenital abnormalities ( p = 0.03). Whether this observation in this small group is reflective of the entire UK test veteran cohort or whether it is selection bias requires further work. The cohort described here represent an important and unique family trio grouping whose participation is enabling genetic studies, as part of the GCFT study, to be carried out. The outcomes of these studies will be published elsewhere. ISRCTN Registry: 17461668.